ANALISIS KIMIAWI AIRFORMASI PADA BATUGAMPING TERSIER DAERAH CISEENG BOGOR - Suherman Dwi Nuryana; Rendy Setiawan; Abdurrachman Asseggaf; Arini Dian (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Ciseeng area of the Bogor Regency is geologically composed by the Quarter Volcano Deposition and Tertiary rocks. The phenomenon of hot springs in the Ciseeng area comes out through cracks in Tertiary-aged limestone. The purpose of this study was to determine the characteristics of formation water based on its chemical parameters. Research methods include the preparation stage; collection and compilation of groundwater data, and water samples; processing phase of groundwater chemical data, and stable isotope content of Oxygen-18 and Deuterium (δ18O and δ2H); and data analysis. Based on the analysis of water quality, formation water that comes out as a Ciseeng hot spring contains a high chloride element (Cl) 23,680.6 mgr/l as a result of reacting with rock minerals derived from the Tertiary rocks below which with water at high temperatures, based on its chemical facies the Ciseeng hot springs, have magnesium type chloride. The results of plotting δ18O and δD and deviations from the global meteoric water line show that the Ciseeng hot spring has the heaviest isotope content.